2010
DOI: 10.1007/s00262-010-0892-3
|View full text |Cite
|
Sign up to set email alerts
|

A novel human recombinant single-chain antibody targeting CD166/ALCAM inhibits cancer cell invasion in vitro and in vivo tumour growth

Abstract: Screening a phage-display single-chain antibody library for binding to the breast cancer cell line PM-1 an antibody, scFv173, recognising activated leukocyte cell adhesion molecule (ALCAM, CD166) was isolated and its binding profile was characterized. Positive ALCAM immunohistochemical staining of frozen human tumour sections was observed. No ALCAM staining was observed in the majority of tested normal human tissues (nine of ten). Flow cytometry analyses revealed binding to 22 of 26 cancer cell lines of variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 33 publications
2
25
1
Order By: Relevance
“…In melanoma, silencing ALCAM expression in high-ALCAM expressed cell line a showed reduction of cell motility and invasiveness (Jannie et al, 2012). Moreover, blocking ALCAM with single-chain antibody inhibited invasiveness of breast cancer (Wiiger et al, 2010). On the contrary, our results showed that blocking ALCAM with the antibody did not affect invasion of CCA even when increasing to very high concentrations.…”
Section: Discussioncontrasting
confidence: 54%
“…In melanoma, silencing ALCAM expression in high-ALCAM expressed cell line a showed reduction of cell motility and invasiveness (Jannie et al, 2012). Moreover, blocking ALCAM with single-chain antibody inhibited invasiveness of breast cancer (Wiiger et al, 2010). On the contrary, our results showed that blocking ALCAM with the antibody did not affect invasion of CCA even when increasing to very high concentrations.…”
Section: Discussioncontrasting
confidence: 54%
“…Wiiger et al (16) described a human recombinant single-chain antibody targeting ALCAM that was able to inhibit cancer cell invasion in vitro and in vivo tumor growth. Furthermore, Roth et al (35) described an internalizing single chain antibody that targets ALCAM in prostate cancer cells and immunoliposomes using this antibody were developed in order to deliver liposomal drugs to prostate cancer cells (35).…”
Section: Alcam Ihc Results ------------------------------------------mentioning
confidence: 99%
“…An association between high ALCAM expression and unfavorable prognosis has been shown for colorectal (7), pancreatic (9) and esophageal squamous cell cancer (8), and neuroblastoma (12). As a membrane protein, ALCAM also represents a potential target for therapy, which has already been successfully targeted by human recombinant single-chain antibody in breast cancer cells (16).…”
Section: Introductionmentioning
confidence: 99%
“…CD166 is involved in hematopoiesis (19,20), neurite extension (21), osteogenesis (22), and embryonic implantation in the uterus (23). The level of CD166 expression correlates with the aggregation and metastatic potential of a few human tumors (24), including melanoma (25,26) and prostate (27,28), ovarian (29), breast (30 -32), colorectal (33,34), esophageal (35), and pancreatic cancer (36,37). Furthermore, AL-CAM was also identified in medium conditioned by breast cancer cells and may be a potential serum breast cancer biomarker (38,39).…”
Section: Discussionmentioning
confidence: 99%